Implementation of Defense Industry Policies in Supporting Maritime Defense in Indonesia - Prasetyo Bekti (AGUSPATI Research Institute, 2022)
This The existence of Indonesia's strategic geographical location, which is located between two oceans and continents, including the Indian and Pacific oceans and the continents of Asia and Australia. Dimann Indonesia is located as a strategic maritime axis, both for various relations and world trade routes. In addition, Indonesia has regulations regarding state sovereignty that must be maintained and guarded from various forms of threats, both from outside and from within. Then Indonesia must have various TNI defense equipment capabilities that are quite adequate and reliable for defense and security tools in maintaining the sovereignty of the Republic of Indonesia and guarding from various disturbances, threats and challenges as well as various obstacles that exist both from abroad and from within the country. For this reason, in overcoming this, the development and development of the defense industry is very necessary. In this study, there are main issues, namely the policy of the defense industry in supporting maritime defense in Indonesia. The method used in this research is qualitative in the form of descriptive and juridical analysis that is needed to analyze problems regarding the implementation of defense industry policies in supporting Indonesian maritime defense due to the strategic location of Indonesia's territory. The results of the analysis and study of the problem show that the defense industry owned by Indonesia is very strategic so that defense equipment has an important role in protecting Indonesia's sovereign territory. The defense industry policy started with the establishment of the KKIP (Defense Industry Policy Committee) based on Presidential Regulation (Presidential Regulation) No. 42 of 2010 and Law (Law) No. 16 of 2012 concerning the defense industry and Presidential Regulation (Presidential Regulation) No. 59 of 2013. On this basis it can show where the defense industry will be developed in the territory of Indonesia, to get a defense industry that has the reliability to produce defense equipment in maintaining the sovereignty of the Republic of Indonesia